ТАЛАБАЛАРНИНГ КАСБИЙ-АМАЛИЙ ЖИСМОНИЙ ТАЙЁРГАРЛИГИ - Шайимарданов, Ш.А. (FAN va JAMIYAT, 2022)
The article deals with the issues of physical development and professionally applied physical training of students of pedagogical universities. The factors that most ensure success in the upcoming work are identified. The materials of the correlation analysis convincingly indicate that the special control exercises and basic gymnastics tools used, which formed the basis of the comprehensive training program, have a high level of significance and are informative.